Pinch Analysis Targeting for CO2 Total Site Planning - Wan Norlinda Roshana, Mohd Nawi; Sharifah Rafidah, Wan Alwi; Zainuddin, Abdul Manan; Klemes, Jiří Jaromír (Springer Berlin Heidelberg, 2016)
Rising CO2 emissions that have been primarily attributed to fossil fuel utilisation have motivated extensive research on optimal CO2 reduction planning and management. Carbon (more precisely CO2) capture and storage (CCS) and carbon capture and utilisation (CCU) have been the potential solutions to control CO2 emissions. However, mitigating CO2 emissions via CO2 storage in geological reservoirs without utilisation is merely a technology transition, and CO2 utilisation is limited due to the short lifespan of products. The integration of CCS and CCU, described as carbon capture, utilisation and storage (CCUS), has recently been introduced as a better option to mitigate CO2 emission. This study introduces a new algebraic targeting method for optimal CCUS network based on a Pinch Analysis–Total Site CO2 integration approach. A new concept of Total Site CO2 Integration is introduced within the CCS development. The CO2 captured with a certain quality from the largest CO2 emissions sources or plants is injected into a CO2 pipeline header to match the CO2 demands for utilising by various industries. The CO2 sources and demands are matched, and the maximum CCU potential is targeted before the remaining captured CO2 is injected into a dedicated geological storage. One or more headers are divided into certain composition ranges based on the purity level of the CO2 sources and demands. The CO2 header can satisfy the CO2 demands for various industries located along the headers, which require CO2 as their raw material. The CO2 can be further regenerated, and mixed as needed with pure CO2 generated from one or multiple centralised CO2 plants if required. The main consideration for the problem is the CO2 purity composition of targeted sources and demands. The proper estimation of CO2 integration will reduce the amount of CO2 emission needed to be stored and introduced to systematic CO2 planning and management network.